ANALYZING THE IMPACT OF GLOBALIZATION ON MINORITY LANGUAGES - Abdumutalibova Mohlaroyim Xabibullo qizi The student of Chirchik State Pedagogical University Scientific advisor: Khamitov Eldorbek Erkin o’g’li (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Globalization, marked by the rapid flow of goods, ideas, and cultural practices across borders, has profoundly influenced linguistic diversity worldwide. While globalization has fostered communication and cultural exchange, it has also contributed to the erosion of minority languages, endangering cultural heritage and identity. This paper examines the multifaceted impact of globalization on minority languages, analyzing factors such as economic pressures, media dominance, and educational policies. The study highlights the tensions between global integration and local linguistic preservation, emphasizing the need for policies that balance linguistic diversity with modernity. By exploring case studies and data from various regions, this research underscores the urgency of safeguarding endangered languages in a rapidly globalizing world. Keywords: Globalization, Minority Languages, Linguistic Diversity, Language Endangerment, Cultural Identity